Innovation : from experimentation to realisation - Papadakis, Alexandra, ....-; Papadakēs, A., ....- (London : New Architecture Group ; [Amsterdam] : Bis, 2003)
New technologies and philosophical concepts have made it possible that ideas that once only existed on paper, have now been realised, enriching the world with exciting and provocative architectural forms. Today, according to Wolf Prix, you can 'only succeed in architecture if your ambition is to create buildings that are visionary in the sense of lay-out, form and structure'. These new ideas, also inspired by science and space travel, have filtered through to the world of business, sport, shopping and entertainment. In this book, innovative projects by the most talked about architects and other designers are portrayed in a breathtaking manner and informatively documented.
"Art, design, architecture, media, fashion"--Cover.
Keywords: Architecture and technology; Architecture -- Technological innovations; Architectuur; Toegepaste kunst